WASTE MINIMIZATION EFFORTS TOWARDS GREEN LOGISTIC AT PT NARDEVCHEM KEMINDO - Agustinus, Bernand Setia; Shilul Imaroh, Tukhas (Dinasti Publisher, 2021)
PT Nardevchem Kemindo is a company in the distribution of raw materials for processed food and beverages industries. The problem studied in this research is that during the 2015 – 2019 period, the waste level occurs in the company’s data always exceeds the company's tolerance limit of 1% and always increases each year. The purpose of this research is to find out the root cause of the waste and to formulate the improvement recommendations for the company to minimize waste as the company's efforts towards Green Logistics. The methods used in this research is the DMAIC concept, followed by the fishbone to identify the root cause of the problem and the FMEA followed by the 5W+1H method to formulate proposed improvements for company. Improvement recommendations for the company are the training for the sales team, installation of air conditioners and thermostat at the warehouse and formulating SOPs for incoming goods inspection.